ANALISIS PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM PEMBANGUNAN PENGAMAN PANTAI DI DESA TEULAGA TUJOH (PUSONG) KECAMATAN LANGSA BARAT - KOTA LANGSA - Thursina Mahyuddin (Universitas Medan Area, 2016)
This research aims to analyze the participation of the community in the implementation of development programs in the villages of Teulaga Tujoh Kecamatan Langsa Barat Kota Langsa and to knowing the factors supporting and restricting the execution of development in the villages of Teulaga Tujoh Kecamatan Langsa Barat Kota Langsa. Descriptive research method using kualitative with the literature and key informants answer results. The study results conclude partisipation community Teulaga Gampong Tujoh (Pusong) Subdistrict of Langsa Timur in the context of the development of coastal protection is still in the stage of manipulation as well as intense as the explanation of notice Arnsteindalam the concept of a ladder of participation.